Contrast‐enhanced echocardiographic detection of severe aortic insufficiency in venoarterial extracorporeal membrane oxygenation. Issue 6 (8th June 2020) - Janus, Scott E.; Hajjari, Jamal; Al‐Kindi, Sadeer; Elgudin, Yakov; Hoit, Brian D.
Abstract: Venoarterial (VA) extracorporeal membrane oxygenation (ECMO) support is an increasingly used temporizing therapy for patients with refractory cardiogenic shock. Contrast‐enhanced echocardiography plays a critical role in the diagnosis and management of diseases that precipitate severe cardiac failure. In this case report, we describe a previously healthy 60‐year‐old woman who presented with dyspnea on exertion, and whose hospital course was complicated by ventricular fibrillation, emergent coronary artery bypass surgery (CABG), and ECMO support. Her contrast‐enhanced ECMO images demonstrated a unique pattern of opacification of three of the four cardiac chambers, which led to a diagnosis of severe aortic insufficiency.